Development of Toulmin Argumentation E-Module to Improve Students’ Argumentation Ability on the Buffer Solution Concept - Yusnidar, Yusnidar; Haryanto, Haryanto; Kurniawan, Dwi Agus; Salsabilah, Wanada Siti; Rizqiyah, Nabila Nur (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop and test the effectiveness of e-modules based on Toulmin argumentation patterns in improving students’ argumentation skills on buffer solution material. This study also aims to confirm that e-modules based on Toulmin argumentation patterns effectively improve students' critical thinking skills and engagement. Methodology: This study uses the Research and Development (R&D) method with the ADDIE development model. The research sample was grade XI MIPA students selected purposively, consisting of an experimental class using e-modules and a control class with printed modules. Main Findings: The e-module was considered very feasible to use, with an average score of 90% in content, learning design, and readability. The effectiveness test showed that the post-test score of the experimental group (85.3) was significantly higher than the control group (73.1), with p < 0.05. The Toulmin pattern component increased significantly, and 92% of students responded positively despite minor technical constraints. Novelty/Originality of this study: The novelty in applying the Toulmin argumentation pattern as the primary approach in developing E-Modules aims to improve students’ argumentation skills in learning buffer solutions. This study shows that e-modules based on Toulmin Argumentation Patterns effectively improve students’ logical argumentation skills, critical thinking, and conceptual understanding in chemistry learning. Integrating digital technology encourages active engagement and the development of higher-order thinking skills. These implications emphasize the importance of digital innovation for transforming 21st-century learning.